Breaking down the blood-brain barrier: signaling a path to cerebral malaria? - Adams, S; Brown, H; Turner, G (2002)
Cerebral malaria is a major killer in the developing world, but we still know very little about the causes of this disease. How does Plasmodium falciparum cause such a devastating neurological disease while it is in the brain vasculature? Why do some patients die, whereas others survive? What processes contribute to disease in the brain, and can we reverse them? Here, the latest evidence from post-mortem, in vitro and animal studies is reviewed to highlight the role of blood-brain barrier breakdown in cerebral malaria. Blood-brain barrier integrity is disturbed during severe malaria, causing leakage of cerebral vessels. Understanding how this happens and how it contributes to the pathogenesis of coma may provide new opportunities for the treatment of cerebral malaria.